Assessing the impact of career competence on learning outcomes of accounting– auditing students in Hanoi, Vietnam (International Journal of Scientific Research and Management (IJSRM), 2024)
The Vietnamese economy is entering a period of increasingly rapid integration and profound development across all sectors. To adapt to these changes, the workforce in all industries, including the field of accounting and auditing, must meet professional competency requirements. Therefore, the development of competency – oriented training programs for accounting– auditing students during their university education is receiving growing attention and emphasis from society. This has led to the necessity of evaluating the impact of professional competencies on academic performance to identify solutions for improving learning outcomes and enhancing students’ ability to apply knowledge in their future careers. The study employs a quantitative method to survey and investigate 316 accounting and auditing students from 13 different universities in Hanoi. With 309 valid responses collected, data analysis reveals that the factor of Knowledge has the strongest influence on academic performance, followed by Attitude, Skills (Hard Skills and Soft Skills), as well as Information technology proficiency and English proficiency. Based on these findings, the paper assesses the degree of influence and provides relevant recommendations to improve the learning outcomes of university students.